A.I. Artificial intelligence - Kennedy, Kathleen, 1954-; Spielberg, Steven, 1946-; Curtis, Bonnie; Osment, Haley Joel, 1988-; Law, Jude, 1972-; O'Connor, Frances, 1970-; Gleeson, Brendan; Robards, Sam.; Hurt, William; Kaminski, Janusz, cinematographer; Kahn, Michael; Williams, John, 1932-; et al. ([United States] : DreamWorks Home Entertainment, 2002)
Visions of a future full of astonishing android technology. David, an advanced android, embarks on an extraordinary adventure to discover the secret of his own identity. Believing in the story of Pinocchio, David dreams of becoming a real boy.
DVD, DTS, Dolby digital 5.1, Dolby digital 2.0 surround.
English or French dialogue, English or Spanish subtitles.
Haley Joel Osment, Jude Law, Frances O'Connor, Brendan Gleeson, Sam Robards, William Hurt.
Director of photography, Janusz Kaminski ; editor, Michael Kahn ; music, John Williams ; costume designer, Bob Ringwood ; production designer, Rick Carter ; robot character design and animatronics by Stan Winston.
Based on the short story "Supertoys last all summer long" by Brian Aldiss.
MPAA rating: PG-13.
Keywords: Androids -- Drama; Artificial intelligence -- Drama; Dreams -- Drama; Feature films; Video recordings; Science fiction films; Video recordings for the hearing impaired